Changes in Outpatient Opioid Prescribing During the COVID-19 Pandemic: An Interrupted Time Series Analysis. (February 2022) - Rikin, Sharon; Perez, Hector R.; Zhang, Chenshu; Khalid, Laila; Groeger, Justina; Deng, Yuting; Starrels, Joanna L.
Objectives: Changes in health care delivery during the COVID-19 pandemic may have impacted opioid prescribing. This study evaluated the impact of restrictions on in-person care on opioid prescribing in the outpatient setting. The hypothesis was that after restrictions to in-person care were implemented, there would be a reduction in the number of chronic and non-chronic opioid prescriptions. Methods: An interrupted time series analysis was conducted to compare the number of weekly opioid prescriptions between baseline (1/1/2019-3/14/2020), restriction (3/15/2020-6/6/2020), and reopening (6/7/2020-10/31/2020) periods at outpatient practices within a health system in Bronx, NY. Analyses were stratified by prescription type (chronic if the patient had been prescribed opioids for >90 days, or non-chronic). Results: For chronic opioid prescriptions, the week restrictions were implemented, there was an increase in the number of prescriptions compared to what was predicted if there had been no interruption (34.8 prescriptions, 95% CI: 8.0, 61.7). Subsequently, the weekly trend in prescribing was not different in the restriction period or in the reopening period compared to the previous time periods. For non-chronic opioid prescriptions, during the restriction period, the weekly trend in prescribing decreased compared to baseline (−5.0 prescriptions/week, 95% CI: −9.0, −1.0). Subsequently, during the reopening period, the weekly trend in prescribing increased compared to the restriction period (6.4 prescriptions/week, 95% CI: 2.2, 10.7). Conclusions: Despite abrupt restrictions on in-person care, chronic opioid prescriptions did not decrease, which is evidence that providers evolved to meet patient needs. Changes in non-chronic prescriptions are likely related to patients electing not to pursue care for acute pain or challenges with appointment availability.